1981
DOI: 10.1002/crat.19810160814
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Debye temperature of diamond‐like semiconducting compounds by means of the Lindemann rule

Abstract: Application of the Lindemann rule t o the estimation of the Debye temperature 8 of diamond like semiconducting compounds is discussed. The classical formula of LINDE-YANN was modified by a constant K,: 8 = Kl vT,/A . v2/3 + K,. The constants Kl and K , are given for AIIIBV, AIIBVI, AIIBIVCz and AIBIIICTI compounds. These were calculated as well from X-ray diffraction data as from 8 evaluated from specific heat capacity and elastic constants.Es wird die Anwendung der Lindemann-Regel zur Abschiitzung von Debye-T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

1983
1983
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…At room temperature the effective value of Θ XR was found to be 227±5 K. The Debye temperatures Θ D were also calculated from the melting temperature T m using the Lindemann approximate formulas given for the chalcopyrite semiconducting compounds A 1 B 3 C 6 2 in [22,23]. It is known that the value of Θ D depends on both the method and temperature of measurement, and the method of determining the Debye temperature influences on the Lindemann constants.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…At room temperature the effective value of Θ XR was found to be 227±5 K. The Debye temperatures Θ D were also calculated from the melting temperature T m using the Lindemann approximate formulas given for the chalcopyrite semiconducting compounds A 1 B 3 C 6 2 in [22,23]. It is known that the value of Θ D depends on both the method and temperature of measurement, and the method of determining the Debye temperature influences on the Lindemann constants.…”
Section: Resultsmentioning
confidence: 99%
“…The Θ D C values at 0 K for the same chalcopyrite compounds were derived from the low temperature heat capacity measurements [22][23][24][25]. Using these data the following relationships were found [22,23]:…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the 0o values from [10][11][12], we fitted relation (1) to the measured heat capacities (Figs 1 and 2) with the parameters N and ck as adjustable parameters. We found that a value of N = 3 must be used in all cases.…”
Section: Resultsmentioning
confidence: 99%